PENGARUH ASPEK SIRKULASI DALAM MEMBENTUK INTEGRASI RUANG TERBUKA PUBLIK PADA SEBUAH PUSAT PERBELANJAAN (Studi Kasus : Mall Kelapa Gading, Lippo Mall Kemang, dan Paris Van Java) - Aryani Widyakusuma (Jurnal KaLIBRASI - Karya Lintas Ilmu Bidang Rekayasa Arsitektur, Sipil, Industri, 2019)
The lack of public open space due to the land competition in urban area generates less activity to gather in community, because of this changing of the life style, people who used to gather in public open spaces now moving to gather in modern shopping centers. This led to the development of shopping center design that integrated with public open space as a forum for the community to gather. This research takes a case study in Paris Van Java Mall Bandung (West Java), Mall Kelapa Gading (DKI Jakarta), and Lippo Mall kemang (DKI Jakarta). These three shopping centers is integrated with public open space. The purpose of this research is to find a form of integration of public open spaces to the shopping centers, especially in the aspect of circulation, zoning activities, and visual space. The method use in this research is descriptive qualitative method with a case study approach. Methods of data collection are using place-centered mapping and person-centered mapping. The results of this research indicate that circulation aspects use camouflaging approach by the linear arranged retails, that visitors can pass through the space between retails whose circulation form with semi open space. The aspect of zoning activity will form zoning receiver, zoning connections, zoning support (retail, sitting area, garden), and multiuse zoning. The aspect of visual space will be dominated by the space and the principle of rhythm, so that the visual of the space would provide unity between public open space and shopping center.Keyword: integration, public open space, shopping center